Impact of the COVID-19 pandemic on vulnerable groups through the gaze of nursing students: an educational project with Photovoice - Elena Andina Díaz (2021)
New teaching strategies for higher education suggest integrating dynamic methodologies. Thus, university students’ critical thinking can be actively worked. Reflective photography or photovoice has been used in the educational field to form knowledge about the social context. Goals: To develop an educational project where critical thinking is promoted in nursing students using photovoice. Methods: Participatory Action Research, specifically photovoice. The educational project was carried out in three different geographical areas: nursing students from the University of León (Spain), Alicante (Spain) and Southampton (United Kingdom). The chosen topic was the impact of COVID-19 pandemic on lower socioeconomic groups and ethnic minorities. The students accessed the community context and photographed this impact. Each photograph was accompanied by an explanation (narrative). Then, a discussion group was conducted in seminars where they analysed the photographs/narratives qualitatively, establishing categories. Photographs were selected to represent each category. Finally, a photographic exhibition was built to promote reflection at the community level. Results: 84 students participated in the project. The categories "hunger", "homeless", "disadvantaged neighbourhoods", "working in the streets", "silence in the streets" and "ethnic minorities" emerged from the data and served as a thread for students to reflect on the impact of COVID-19 pandemic on these vulnerable groups. Conclusions: This educational project, which used the photovoice tool, showed how critical thinking was promoted in students across different countries. Photovoice seems to be an original, simple, and inexpensive tool to encourage university students' critical thinking regarding the social and cultural dimensions of health. This is relevant since they are the future promoters of community health changes.